LASER TARGET TRACKING - SALIMAN, MUHAMMAD SHAZRIN (2017)
In conjunction with the increases of accident that root out from lack of focus to the roads, the needs of a detection system that able to provide early detection are increasing. This type of system will be able to alert the driver and increase the time to react with the incoming object. The implementation of the system are expected to reduce the number of accident or at least reduce the causalities of the accident tremendously.